Playground injuries in children - Naeini H; Lindqvist K; Jafari HR; Mirlohi AH; Dalal K (Dove Medical Press, 2011)
Hassan Sadeghi Naeini1, Kent Lindqvist2, Hamid Reza Jafari3, Amir Hossein Mirlohi4, Koustuv Dalal2,51Iran University of Science and Technology, Tehran, Iran; 2Division of Social Medicine and Public Health, Department of Medical and Health Sciences, Linköping University, Linköping, Sweden; 3Environmental Planning Department, Graduate Environment Faculty, University of Tehran, Tehran, Iran; 4Apadana Research Center, Isfahan, Iran; 5Division of Public Health Science, School of Life Sciences, University of Skovde, SwedenBackground: Rapid urbanization and unplanned population development can be detrimental to the safety of citizens, with children being a particularly vulnerable social group. In this review, we assess childhood playground injuries and suggest safety mechanisms which could be incorporated into playground planning.Methods: Inclusion criteria were “children” as the focus group, “playground” as the main field of study, and “unintentional injury” and “safety” as the concepts of study. The keywords used for the PubMed search were “playground”, “children”, and “injury”. Initially we accessed 182 articles. After screening according to inclusion criteria, 86 articles were found, and after reading the abstracts and then the full text, 14 articles were finally included for analysis. The papers reviewed included four case-control studies, three case studies, three descriptive studies, two interventional studies, one retrospective study, one cross-sectional study, and one systematic review.Results: Playground-related fractures were the most common accidents among children, underscoring the importance of safety promotion and injury prevention in playgrounds, low-risk equipment and playing hours (week days associated with higher risk), implementation of standards, preventing falls and fall-related fractures, and addressing concerns of parents about unsafe neighborhoods. With the exception of one study, all of the reviewed papers had not implemented any practical safety plan. Safe engineering approaches were also ignored.Conclusion: We recommend a systematic safety approach based on the “safety circle” which includes three main areas, ie, equipment, environment, and children.Keywords: children, playground, injury, safety